Pengenalan Database Management System (DBMS) - M. Riyan Dirgantara; Salsabila Syahputri; Adelia Hasibuan; Nurbaiti N (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The purpose of this article is to provide a comprehensive understanding of database management and its role in modern business. The article also aims to introduce readers to various technologies and methods used in database management, as well as the stages involved in implementing database management. The author's method is literature review, a research method that involves collecting and analyzing data from literature sources such as books, journals, articles, and other documents to answer research questions. A database is a collection of related data stored together with controlled redundancy to serve one or more applications optimally. Data is stored independently of the program used to access it, and adding, modifying, and retrieving existing data is common and controlled. The article also defines a database as a logically related collection of data stored together, designed to meet the information needs of an organization, and as an electronic archive storage system. The article explains three database components, namely field, record, and file.